MEMS Lorentz Force Magnetometers From Specifications to Product - Buffa, Cesare; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book deals with compasses for consumer applications realized in MEMS technology, to support location-based and orientation-based services in addition to 'traditional' functionalities based on navigation. Navigation is becoming a must-have feature in portable devices and the presence of a compass also makes location-based augmented reality emerge, where a street map or a camera image could be overlaid with highly detailed information about what is in front of the user. To make these features possible both industries and scientific research focus on three axis magnetometers. The author describes a full path from specifications (driven by customers' needs/desires) to prototype and preparing the way to industrialization and commercialization. The presentation includes an overview of all the major steps of this research and development process, highlighting critical points and potential pitfalls, as well as how to forecast or mitigate them. Coverage includes system design,specifications fulfillment, design strategy and project development methodology, in addition to traditional topics such as microelectronics design, sensor design, development of an experimental setup and characterization. The author uses a practical approach, including pragmatic guidelines and design choices, while maintaining focus on the final target, prototyping in the direction of industrialization and mass production.
Introduction -- From specifications to concept -- Lorentz force magnetometers -- System design -- Sensor design and fabrication -- A custom instrument for electromechanical characterization -- Device electromechanical characterization -- Driving and readout electronics: a discrete components solution -- ASIC design -- From prototype to product -- Conclusion.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation